Traditional versus computer-mediated approaches of teaching educational measurement. - Alkharusi H; Kazem A; Al-Musawai A (Journal of Instructional Psychology, 2010)
Research suggests that to adequately prepare teachers for the task of classroom assessment, attention should be given to the educational measurement instruction. In addition, the literature indicates that the use of computer-mediated instruction has the potential to affect student knowledge, skills, and attitudes. This study compared the effects of a traditional face-to-face instruction of an undergraduate level educational measurement course to a computer-mediated instruction on academic course performance, educational measurement knowledge, skills , and attitudes of teacher education students (N =51) at Sultan Qaboos University in Oman, using a posttest-only control group design. Results revealed statistically significant group differences favoring the computer-mediated instruction. Implications and recommendations for educational measurement instruction and research are discussed.